Psychological repercussions of breast or uterine cervical cancer disclosure to women in Gabon. - Béa-Christelle Ndjengue Bengone; Jean Toniolo; Angela-Christie Filankembo Kava; Edgard Brice Ngoungou; Ernest Belembaogo; Pierre-Marie Preux (PLoS ONE, 2025)
Background Breast and cervical cancers are major health issues globally, with particularly high burdens in sub-Saharan Africa, including Gabon. Limited epidemiological data and insufficient attention to the psychological impacts of these cancers highlight critical research gaps. This study aimed to explore the psychological repercussions experienced by Gabonese women following the disclosure of a breast or cervical cancer diagnosis. Methods A mixed-methods cross-sectional study was conducted from March to May 2023 at the Institut de Cancérologie d'Akanda. Women recently diagnosed with breast or cervical cancer were recruited using a consecutive sampling method. Data were collected through semi-structured individual interviews and one focus group to explore emotional responses, coping strategies, and perceptions of patient-provider interactions. In addition, the Patient Health Questionnaire-9 (PHQ-9) was administered to assess depressive symptoms. Results Thirteen Gabonese women diagnosed with breast (n = 10) or cervical cancer (n = 3) participated in this mixed-methods study. Following the disclosure, all patients reported depressive symptoms ranging from minimal to moderately severe (PHQ-9). Qualitative analysis revealed intense emotional distress, including anxiety, sadness, sleep disturbances, and despair. The diagnosis affected participants' identity, body image, and social relationships, reinforcing feelings of stigma, isolation, and loss. Beliefs about disease etiology and social representations shaped emotional responses. While some relied on spirituality, social support, or personal resilience to cope, others expressed unmet psychological needs. Participants emphasized the importance of clear, compassionate communication from healthcare professionals, highlighting the need for empathy, trust, and active listening during diagnosis disclosure. Conclusion This pioneering study in Gabon identifies profound psychological effects associated with breast and cervical cancer diagnosis disclosure. The findings underscore the urgent need for improved psychosocial support, effective communication training for healthcare providers, and culturally tailored interventions to address mental health concerns in this population.